Nonstring Music Teachers’ Comfort Teaching String Ensembles - Kim, Ji-Eun (Jen) (String research journal, 2023)
This study was designed to explore nonstring specialists’ comfort teaching students in string ensembles. Comfort was defined as an individual’s ease when teaching the subject matter. Data were gathered, using a 7-point Likert-type scale related to 15 string topics administered through a researcher-developed study. Participants (N = 180), who were identified through the National Association for Music Education membership list, were contacted via email. Responses were analyzed using descriptive and parametric statistics. Results revealed that band specialists felt significantly more comfortable in string teaching situations than choir and elementary general music specialists. Participants who took a string methods course, as compared with those who did not, felt more comfortable teaching seven specific string topics. Participants who were currently teaching string ensembles felt more comfortable teaching all string topics, except for vibrato technique. Participants who had taught strings in the past were significantly more comfortable teaching string ensembles than those who had never taught strings. The findings of this study could help higher education string methods instructors select instructional activities and course topics that were revealed to provide the most beneficial experiences.